2015
DOI: 10.1039/c5cp02172c
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopy of protonated leu-enkephalin and its 18-crown-6 complex embedded in helium droplets

Abstract: Ultracold IR spectra of the protonated five amino acid peptide leu-enkephalin (Tyr-Gly-Gly-Phe-Leu) embedded in superfluid helium droplets have been recorded using a free-electron laser as radiation source. The results show resolved spectra, which are in good agreement with theoretical calculations, as well as with the available gas-phase data indicating that the helium environment does not induce a significant matrix-shift. In addition, the effect of the interaction between the charge and the peptide backbone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 32 publications
2
53
0
2
Order By: Relevance
“…While the mechanism of the ejection process is not entirely understood, the technique itself is pivotal for ion spectroscopy. Recent experiments revealed that the intensity of the ejection signal rises faster than linear with the laser pulse energy [198]. This effect indicates a nonlinear character of the ejection, and may potentially complicate the interpretation of the results.…”
Section: Molecular Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism of the ejection process is not entirely understood, the technique itself is pivotal for ion spectroscopy. Recent experiments revealed that the intensity of the ejection signal rises faster than linear with the laser pulse energy [198]. This effect indicates a nonlinear character of the ejection, and may potentially complicate the interpretation of the results.…”
Section: Molecular Ionsmentioning
confidence: 99%
“…While resonance multiphoton ionization is only feasible with specific molecules, electrospray ionization (ESI) provides a universal technique for bringing large ions, such as proteins, into the gas phase [195,196,[198][199][200]. However, the low density of ions in electrospray has warranted a considerable modification of the pickup technique which involves ion traps.…”
Section: Molecular Ionsmentioning
confidence: 99%
“…Here alignment refers to confinement of molecular axes to axes fixed in the laboratory frame -typically defined by the polarization vectors of the laser pulses employed [5,6]. The transfer of laser-induced alignment techniques from gas-phase molecules to molecules in He droplets opens new opportunities such as extending the range of molecular systems amenable to alignment -notably to larger molecules, clusters and complexes [7][8][9], conducting experiments on aligned molecules in the presence of a dissipative environment [1,10,11] and possibly using controlled rotation of molecules [12] to study the properties of He droplets [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Florez et al recorded the vibrational spectra of [Leu-Enk + H] + and its complex with crown-16 [Leu-Enk + CE + H] + embedded in helium droplets. 16 Based on the small spectral shift, the authors confirmed the weak interaction between the dopant – albeit charged – with the helium environment. Our group has examined the effects of kinetic energy and droplet size on the doping efficiency using a different approach.…”
Section: Introductionmentioning
confidence: 92%